Association Between Venous Thrombosis (VT) and Pregnancy: A Literature Review: Hubungan Antara Trombosis Vena (VT) dan Kehamilan: Sebuah Tinjauan Literatur - Dalis, Noor Salman (Universitas Muhammadiyah Sidoarjo, 2024)
The incidence of VTE varies across countries, with Eastern regions generally reporting lower rates. In pregnancy, a combination of intrinsic factors, such as hormonal changes, increased blood clotting tendency, and genetic predispo-sitions, along with environmental factors like lifestyle and healthcare access, can trigger VTE through various, often overlapping mechanisms. The precise role of certain risk factors and their interactions during pregnancy remains un-clear and warrants further study. Ongoing research into pregnancy-related VTE is crucial due to the considerable number of idiopathic cases and the need to refine risk stratification methods. Understanding how different risk factors interact during pregnancy can lead to more effective prevention strategies and targeted treatments. As new risk factors are identified, they may help clarify the underlying mechanisms of VTE in pregnancy, particularly in cases where the cause is unknown. Additionally, improving risk stratification not only helps prevent the initial occurrence of VTE in pregnant women but also plays a vital role in reducing the likelihood of recurrence, ultimately leading to better out-comes for both the mother and the child, as well as more efficient use of healthcare resources. Highlights: VTE in Pregnancy: Hormonal, genetic, and environmental factors contribute. Research Needs: Clarify interactions, refine risk stratification, prevent idiopathic cases. Outcomes: Better maternal-child health, reduced recurrence, efficient healthcare use. Keywords: Venous thrombosis, Thrombosis, Cerebral Venous Sinus Thrombosis, Coagulation, pregnancy.